1986
DOI: 10.1210/jcem-63-6-1300
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Somatomedins and Somatomedin-Binding Protein in Pregnant Women with Type I or Gestational Diabetes and Their Infants*

Abstract: The serum levels of the low mol wt form of somatomedin-binding protein (SMBP) were 5-fold higher in both diabetic (n = 44) and nondiabetic pregnant women (n = 14) than in nonpregnant women. No difference was found between women with type 1 diabetes and those with gestational diabetes. There was a negative correlation between maternal levels of SMBP during the last trimester and the birth weight percentile of the infants (r = -0.51). There was a 2- to 3-fold elevation of maternal insulin-like growth factor (IGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
52
0
5

Year Published

1988
1988
2006
2006

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 27 publications
7
52
0
5
Order By: Relevance
“…On the one hand, results from rat studies indicate that maternal serum IGF-I targets the mother's own anabolism and substrate retention rather than the foetus (Gargosky et al 1991, Monaco & Donovan 1996. On the other hand, in humans (Hall et al 1986, Holmes et al 1998) and guinea pigs (Sohlström et al 2001) maternal IGF-I seems to be associated with foetal and placental growth. Maternal plasma levels of IGF-II have been shown to promote the structural development of the placenta (Roberts et al 2001b) and IGF-II produced by the trophoblasts has been suggested to be important for implantation and placentation (Hamilton et al 1998, Han et al 1999, Rutanen 2000.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, results from rat studies indicate that maternal serum IGF-I targets the mother's own anabolism and substrate retention rather than the foetus (Gargosky et al 1991, Monaco & Donovan 1996. On the other hand, in humans (Hall et al 1986, Holmes et al 1998) and guinea pigs (Sohlström et al 2001) maternal IGF-I seems to be associated with foetal and placental growth. Maternal plasma levels of IGF-II have been shown to promote the structural development of the placenta (Roberts et al 2001b) and IGF-II produced by the trophoblasts has been suggested to be important for implantation and placentation (Hamilton et al 1998, Han et al 1999, Rutanen 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Although maternal IGF-I and IGF-II concentrations were not different between normal and diabetic patients during gestation, there was a significant increase in both IGF-I and IGF-II in the cord blood of infants of diabetic mothers, indicating a different regulation of IGFs in mother and fetus. A significant increase in cord IGF-II but not IGF-I in newborns of diabetic mothers was reported by Hall et al [17]. There was no change in either IGF-I or IGF-II in one study [18].…”
Section: Relation Between Birth Weight and Serum Concentrations Of Fementioning
confidence: 60%
“…The abovementioned reports failed to detect any correlation between the two in non-diabetic pregnancy [11][12][13][14], whereas some reports suggested a positive role of IGF-II in fetal growth [9,10]. Hall et al [17] Thus, a combination of both IGFs would be important in promoting fetal growth. It has been established that both IGF-I and -II are produced not only in fetal tissues [30,40] but also by the placenta, suggesting an autocrine/paracrine role of IGFs in placental growth [41].…”
Section: Relation Between Birth Weight and Serum Concentrations Of Fementioning
confidence: 96%
See 1 more Smart Citation
“…Although the potential exists for altered bioavailability of IGFs the actual effect of this protease on IGF delivery to the tissues during pregnancy is not known. Compared with non-pregnant values, when measured by RIA, maternal IGFBP-1 levels increase rapidly, peak in the first trimester (Rutanen et al 1982, Wang et al 1991b and have been shown to correlate inversely with birthweight (Howell et al 1985, Hall et al 1986). Maternal IGFBP-2 concentrations appear to decrease on ligand blotting (Giudice et al 1990); however, the levels measured by RIA are variably reported to be low-normal (Schwander & Mary 1993) or to increase .…”
Section: Introductionmentioning
confidence: 99%